Hearing Threshold Levels among Clothes Convection Industry Workers in Klaten, Central Java, Indonesia (International Journal of Occupational Safety and Health, 2024)
Introduction: Noise-induced hearing loss is a condition that develops gradually and often goes unnoticed due to the absence of observable symptoms. Noise-induced hearing loss is usually detected after effects on hearing ability, difficulty understanding speech, and communication disorders. This study aims to determine the prevalence of hearing threshold decline in workers in the clothes convection industry in Klaten, Central Java, Indonesia.Methods: A cross-sectional study, with 21 respondents, was conducted from April to June 2023. Data were collected through interviews, measurement of noise levels in the workplace, otoscopic and audiometric examinations, and research questionnaires.Results: Most study respondents were female (85.7%) and workers who had worked for 11-20 years (66.7%). The main results showed that the prevalence of decreasing hearing threshold among workers in this study was 33.3%.Conclusion: The prevalence of hearing threshold decline was correlated with length of work and use of ear protection equipment.